(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
In this article, the process of forming the autopedagogical competence of the future teacher of technological education and creative pedagogical individuality has not been sufficiently studied, and the problems of studying the training of personnel based on creative approaches have been analyzed.